Analisis Kepuasa Pelanggan E- Commerce Venus Di DKI Jakarta Ditinjau Dari E-Service Quality - Hatta, Holila; Rumahorbo, Samra Ginola Roberto (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
This study aims to find out the customer satisfaction of E-commerce Venus based on E-Service Quality. This study uses seven E-Service Quality dimensions consisting of efficiency, fulfilment, system availability, privacy, responsiveness, compensation, and contact. This study used Importance Performance Analysis (IPA) method to determine the attributes that made customers not satisfying. The result showed that the customers are satisfied with E-commerce Venus service’s but there are some improvement to do. Based on IPA analysis, E-commerce Venus there are no attributes on top priority to improve and ten attributes must be maintained. But, there are four indicators that have high gap values that E-commerce Venus needs to improve.